Effet de l’apport anthropique sur le développement embryonnaire de l’oursin commun paracentrotus lividus - Belghachem, sarrah (My University, 2023)
The edible sea urchin Paracentrotus lividus (Lamarck, 1816) is the subject of many works that deal with the biology of this species, it constitutes a material of choice in the field of environmental toxicology. This master’s work focuses on determining the sensitivity of embryonic development in sea urchins «Paracentrotus lividus» in the Mostaganem region. For this purpose we carried out three samples (February, March and April) from two study stations, namely the port of Salamander and the stidia station, each known for its different biotic and abiotic properties, at a rate of 10 sea urchins per site and per month, which refers to a total of 60 specimens. Bioassay (bioassay) is a technique frequently used to assess the biological effects of pollutants on marine organisms. The objective of the experiment is to identify toxic effects on populations representative of ecosystems. The results of the exposure of sea urchins to a wide range of pollutants naturally present in the environment are reflected in our study by developmental stoppages, malformations and also growth delays, For example, in stage two, two unequal blastomers were observed, and in the young blastula stage, the membrane is completely shredded and marks a break in division, thus in the prism stage the absence of the second somatic rod in the polluted site
Keywords: Paracentrotus lividus; Salamander harbour; stidia; bioassays; xenobiotics; embryonic malformation